New species and records of Anastrepha (Diptera: Tephritidae) from Brazil - Norrbom, Allen L.; Uchôa, Manoel A. (Zootaxa, 2011)
Three new species of Anastrepha from Brazil are described and illustrated: A. matogrossensis Norrbom & Uchôa (from Mato Grosso), A. oiapoquensis Norrbom & Uchôa (from Amapá), and A. siculigera Norrbom & Uchôa (from Amapá). Anastrepha rafaeli Norrbom & Korytkowski also is reported from the state of Tocantins.